Synthesis, in vitro antitumour activity, and molecular docking study of novel 2-substituted mercapto-3-(3,4,5-trimethoxybenzyl)-4(3H)-quinazolinone analogues - Adel S. El-Azab; Alaa A.-M; Hazem A. Ghabbour; Manal A. Al-Gendy (Taylor & Francis Group, 2017)
A novel series of 2-substituted mercapto-3-(3,4,5-trimethoxybenzyl)-4(3H)-quinazolinones 1-20 was synthesised and evaluated for in vitro antitumour activity. N-(4-Chlorophenyl)-2-[(3-(3,4,5-trimethoxybenzyl)-4(3H)-quinazolinon-2-yl)thio)acetamide (7) and N-(3,4,5 trimethoxybenzyl)-2-[(3-(3,4,5-trimethoxybenzyl)-4(3H)-quinazolinon-2-yl)thio]propanamide (19) exhibited excellent antitumour properties, with mean growth inhibitory concentration (GI50) of 17.90 and 6.33 µΜ, respectively, compared with those of 5-fluorouracil 5-FU, gefitinib, and erlotinib (mean GI50: 18.60, 3.24, and 7.29 µΜ, respectively). Comparison of the GI50 (µM) values of compounds 7 and 19 versus those of 5-FU, gefitinib, and erlotinib against an in vitro subpanel of tumour cells lines showed that compounds 7 and 19 have activities almost equal to or higher than that of those standard drugs, especially against lung, CNS, and breast cancer cells. However, compounds 5, 10, 14, 15, 16, 17, and 20 exhibited effective antitumour activity against the different cell lines tested, with growth inhibition percentage (MGI%) of 19, 24, 19, 17, 16, 15, and 16, respectively. A modelling study was performed for compounds 7 and 19 by docking them into the EGFR kinase enzyme to study their mode of binding with the putative binding site.